Effects of combined ultrasound and low-temperature short-time heating pretreatment on proteases inactivation and textural quality of meat of yellow-feathered chickens. (1st September 2021) - Li, Pengpeng; Sun, Liangge; Wang, Jiankang; Wang, Yuanxin; Zou, Ye; Yan, Zheng; Zhang, Muhan; Wang, Daoying; Xu, Weimin
Highlights: Ultrasound and heating synergistically inactivated proteases of chicken meat. Ultrasound combined low-temperature short-time heating (ULTSTH) inactivation of meat proteases obey the first order kinetics. Compared to chilling, ULTSTH maintains better texture and microstructure of meat. ULTSTH pretreatment inhibited oxidation of breast meat during storage. ULTSTH inactivated the bacteria and extended shelf life of the breast meat. Abstract: This study aimed to investigate the effect of combined ultrasound and low-temperature short-time heating (ULTSTH) (40 kHz, 0.2 W/cm 2 at 55 °C for 15 min) as pretreatment on proteases inactivation and textural quality of yellow-feathered chicken (YFC). Results showed ultrasound and low-temperature heating synergistically improved the inactivation of the most important meat proteases, calpain, cathepsin B and total proteases, with kinetics following the first order decay(s). Degradation of meat proteins was effectively reduced by ULTSTH compared to the pretreatment of chilling. Importantly, ULTSTH increased the firmness of breast meat and led to improved texture and microstructure. Lipid and protein oxidation of meat pretreated with ULTSTH were reduced during refrigerated storage period. Additionally, microorganisms in meat were inactivated by ULTSTH, which resulted in an obvious increase in the shelf life of meat. These findings suggested that ULTSTH is promising as an alternative pretreatment to obtain a favorable textural quality of YFC.